Comparative design of harmonic current reduction in variable speed drive using space vector pulse width modulation and hybrid pulse width modulation - Siregar, Yulianta; Situmeang, Farel; Mohamed, Nur Nabila (Institute of Advanced Engineering and Science, 2024)
In industry and commerce, three-phase induction motors are frequently utilized as the primary power source for machinery. However, to increase motor performance efficiency, induction motors also need a tool for speed control. The variable speed drive (VSD) is one tool used to control the rotation speed of three-phase induction motors. Since VSD is a non-linear load, harmonic distortion will result from it. The space vector pulse width modulation (SVPWM) injection method and the hybrid pulse width modulation method were the two techniques employed by the author in this study to lower the current in the VSD. With the SVPWM injection approach, the variable speed drive's current total harmonic distortion (THD) values in the R, S, and T phases dropped to 3.77%, 3.53%, and 2.19% from 7.14%, 7.17%, and 7.58%.